Pendidikan Islam Berbasis Maqasid Syariah: Membangun Sistem Pembelajaran yang Berorientasi Kesejahteraan Umat - Ayuk Witria Ningsih; Hidayati Nilam Permatasari; Putri Anjani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the concept of maqasid sharia (sharia goals) as the main foundation in Islamic education. With this approach, it is hoped that the Islamic education system can create individuals who not only understand religious values, but are also able to contribute to the welfare of the people. This research provides guidance on the implementation of maqasid sharia-based education at various levels of education, from elementary school to university.